A dinâmica da entrada de turistas estrangeiros no Rio Grande do Sul e sua relevância para o Geoparque Raízes de Pedra - Carmen Regina Dorneles Nogueira; Victor Paulo Kloeckner Pires; Fátima Regina Zan; Ângela Maria Andrade Marinho; Claudio Gabriel Soares Araújo (Confins)
Rio Grande do Sul is located in the southern portion of Brazil and has peculiarities related to its physical aspects, especially related to climate, relief and cultural aspects resulting from its colonization process, in which the presence of European, Asian and African immigrants, as well as the native population, including indigenous people, stands out. The location of the state in relation to Latin American countries makes it one of the largest gateways for international tourists in the country. According to the State Secretariat of Tourism of Rio Grande do Sul, in 2023 the state was the third gateway for international tourists. However, this flow does not reverberate in the dynamism of local tourism, since mainly Argentine and Uruguayan tourists only “pass through” the state, constituting a “tourist corridor”, when heading mainly to the beaches of the state of Santa Catarina. In this context, this study was carried out, the main objective of which is to prospect possibilities of attracting foreign tourists to the territory of the Raízes de Pedra Project. The same was carried out based on applied research (regarding the purpose), bibliographical and documentary research (regarding the means), using the qualitative method and content analysis to systematize and interpret the data. It was found that the municipalities that make up the territory of the geopark project have been developing joint actions of geoeducation, geotourism and geoconservation since 2021, with the aim of obtaining the “UNESCO Global Geopark” seal and, with this, developing local tourism, taking advantage of the flow of foreign tourists who usually enter Rio Grande do Sul. It was observed that such a proposition requires public and private investments in the diversification of the tourist offer, in infrastructure and in the qualification of the workforce, as well as in the implementation of road and tourist signage with a view to the qualified offer as a way of providing opportunities and instigating the tourist flow that only passes through the territory towards the coast, to dedicate a few days of their season to visit the Raízes de Pedra Geopark.